“An End to Unjust Inequality in the World” - Balmer, Randall (Church history and religious culture, 2014)
Since the emergence of the Religious Right in the late 1970s, American evangelicalism has commonly been associated with conservative politics. An examination of nineteenth-century evangelicalism, however, suggests a different affinity. Antebellum evangelicals marched in the vanguard of social change with an agenda that almost invariably advocated for those on the margins of society, including women and African Americans. Evangelicals were involved in peace crusades and the temperance movement, a response to social ills associated with rampant alcohol consumption in the early republic. They advocated equal rights for women, including voting rights. Evangelicals in the North crusaded against slavery. Although Horace Mann, a Unitarian from Massachusetts, is the person most often associated with the rise of common schools, Protestants of a more evangelical stripe were early advocates of public education, including leaders in Ohio, Michigan, and Kentucky. Some evangelicals, including Charles Grandison Finney, even excoriated capitalism as inconsistent with Christian principles.